Highly selective deethylation of rhodamine B: Adsorption and photooxidation pathways of the dye on the TiO2/SiO2 composite photocatalyst - Feng Chen; Jincai Zhao; Hisao Hidaka (International Journal of Photoenergy)
The photocatalytic degradation of Rhodamine B (RhB) with TiO2 and TiO2/SiO2 in the aqueous dispersion was investigated under both the visible light (λ> 480 nm) and UV irradiation. The detailed photocatalytic oxidative process of RhB under these different conditions was revealed by measurement of the isoelectric points of the catalysts, UV-VIS spectra, HPLC and LC-MS. RhB adsorbs on the surface of TiO2/SiO2 particles by the positively-charged diethylamino group while, in the case of net TiO2, it adsorbs through the negatively-charged carboxyl group under the experimental conditions (pH ∼ 4.3). In the RhB-TiO2/SiO2 system, RhB firstly underwent a highly selective stepwise deethylation process before the destruction of the chromophore structure under visible light irradiation. The average yield of the every deethylation step was higher than 86%. It is confirmed that visible light-induced photocatalytic degradation of dye proceeds on the surface of catalysts rather than in the bulk solution and active oxygen species preferentially attack the molecular portion that connects directly to the surface of catalysts. This work provides a possibility for the modification of the surface characteristics of TiO2 to adsorb effectively the special colored organic molecules in selective mode for selective modification or deeply extent photooxidation.